Vom Friedensprojekt zur Sicherheitsgarantin? Das neue Schutzversprechen der Europäischen Union in Zeiten existenzieller Ungewissheit - Bartenstein, Aline; Hegemann, Hendrik; Merschel, Oliver (Integration, 2022)
This article analyses how and to what extent a new guiding narrative of European integration manifests itself in recent self-portrayals of the European Union (EU) as a guarantor of security and protection. This image creates and reproduces specific conceptions of the EU’s self and its fundamental “raison d'être”. The article shows that security in this context does not primarily denote the defense against concrete threats to the physical security of European citizens or critical infrastructures in a specific policy field. Rather, security is understood as a societal value that includes a much broader and more fundamental promise of stability, comfort and certainty in times perceived as crisis-ridden. The image of the EU as a guardian of comprehensive security and protection thus represents an attempt to provide a response to a widespread perception of a fundamental, often diffuse anxiety regarding the EU’s own ability to cope with current and future challenges facing European societi